2014
DOI: 10.1186/1471-2431-14-208
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen concentration on time to resolution of spontaneous pneumothorax in term infants: a population based cohort study

Abstract: BackgroundLittle evidence exists regarding the optimal concentration of oxygen to use in the treatment of term neonates with spontaneous pneumothorax (SP). The practice of using high oxygen concentrations to promote “nitrogen washout” still exists at many centers. The aim of this study was to identify the time to clinical resolution of SP in term neonates treated with high oxygen concentrations (HO: FiO2 ≥ 60%), moderate oxygen concentrations (MO: FiO2 < 60%) or room air (RA: FiO2 = 21%).MethodsA population ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Approximately 1-2% of term and 5-7% of preterm infants have evidence of a spontaneous pneumothorax on chest X-ray, although few are clinically significant. 4 If the pneumothorax is thought to be contributing to significant respiratory distress or is haemodynamically significant, thoracentesis and chest tube placement may be beneficial. 3 Risk factors for neonatal air leak include: prematurity, meconium aspiration syndrome, c-section, pulmonary hypoplasia and mechanical ventilation (particularly with excessive, prolonged or high inspiratory pressures).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1-2% of term and 5-7% of preterm infants have evidence of a spontaneous pneumothorax on chest X-ray, although few are clinically significant. 4 If the pneumothorax is thought to be contributing to significant respiratory distress or is haemodynamically significant, thoracentesis and chest tube placement may be beneficial. 3 Risk factors for neonatal air leak include: prematurity, meconium aspiration syndrome, c-section, pulmonary hypoplasia and mechanical ventilation (particularly with excessive, prolonged or high inspiratory pressures).…”
Section: Discussionmentioning
confidence: 99%
“…15 In a few studies in the pediatric population, supplemental oygen use was not associated with a faster resolution of spontaneous pneumothorax. 18,19 Occasionally we may encounter asymptomatic patients with pneumothorax of large size refusing placement of ICT and surgery. These patients cannot be sent home without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some animal studies have shown that increasing the fraction of inspired oxygen accelerates the resolution rate (4,11). However, recent neonatal studies reported no association between oxygen therapy and resolution rate (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of clinical evidence for the effectiveness of oxygen therapy for primary spontaneous pneumothorax (PSP), which usually occurs in young adults or adolescents. Recent studies reported no association between oxygen therapy and the resolution rate of neonatal pneumothorax (7,8). We conducted a retrospective study to evaluate the effect of oxygen therapy on the resolution rate of PSP.…”
Section: Introductionmentioning
confidence: 99%